PENINGKATAN KETERAMPILAN PROSES SAINS DASAR DALAM MENGGUNAKAN ALAT UKUR PADA PEMBELAJARAN FISIKA DI SMA NEGERI 6 SKOUW JAYAPURA - Albert Lumbu; Florentina Maria Panda (JURNAL PENGABDIAN PAPUA, 2018)
One approach to teachers use were to develop students were creativity the process of science skills. The purpose of KPS themselves approach to train students to think independent, Their backs on this scientific and skilled in work on those problems and is feasible to be invented the concept of play an independent. Some of research shows that many students crisis scientific ability demonstrated by the scientific low performance students are low mastery (KPS) where students are not used to observe activities, classifying, interpreting, proposed hypothesis, using tools and materials, experiment, and other activities that uses scientific method. The purpose of devotion it is 1) to provide information on how to operate a measuring instrument in learning physics senior high school 6 Skouw Jayapura, and 2) train students in is using a measuring instrument so that it can be improved the skills of the process of the basic science in their senior high school 6 Skouw Jayapura. Facets devotion this is done through the training to train students use the gauge in learning physics to improve the ability to the basic science. The achievement of this target from the activities of devotion , satisfactory results or benefit to students in learning high school physics 6 skouw in terms of land : (1) provided information about how to use the gauge in experiments simple, (2) upgrading skill process of basic science in learning physics. Keywords: Jayapura, Measuring Tool, The Science Skills